Oxford practice grammar : basic : with answers. - Coe, Norman, ....-; Harrison, Mark, 1955-; Paterson, Ken, 1958- (Oxford : University Press, 2006)
The first level in the Oxford Practice Grammar series. Grammar topics explained simply and clearly with lots of opportunity to practise. Oxford Practice Grammar knows that students need different types of explanation and practice at each stage of their study. Basic provides lots of practice and short explanations. Great for the classroom or for self-study.
Keywords: Engelse spraakkunst